Oralność bałkańskich opłakiwań na tle tradycji antycznej - Walczak-Mikołajczakowa, Mariola; Mikołajczak, Aleksander W. (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2015)
This article concerns the problems of connections between the Balkan tradition of mourning for the dead and similar practices in Ancient Greece. The present authors are attempting to establish an anthropological context in the performance of mournful songs. The orality is understood not only as a form of oral communication but also as an element of funeral rites. The objects of our analysis are poetic texts of mourning rituals for the dead from the terrains of Bulgaria and Macedonia and the preserved elements of ancient Greek elegies. The author present a reconstruction of situations which were being enacted. They pay special attention to the similarities connecting Balkan folklore and ancient Greek heritage. In this way they indicate the universal anthropological dimension of both traditions, which is present in orality.
Keywords: oralność; antropologia; staroserbska tradycja oralna; Bałkany